Stabilized diverse HIV-1 envelope trimers for vaccine design - Qian Wang; Bingting Ma; Qingtai Liang; Angqi Zhu; Hua Wang; Lili Fu; Xiaoxu Han; Xuanling Shi; Ye Xiang; Hong Shang; Linqi Zhang (Emerging Microbes and Infections)
One of the major goals in HIV-1 vaccine development is to achieve properly folded and stabilized envelope glycoprotein (Env) trimers that mimic the native Env on the mature virion. Here, we design and characterize uncleaved prefusion-optimized (UFO) trimers for 12 Envs currently circulating in China. Biochemical and biophysical characterization of these UFO trimers identified two subtype B/Bʹ Envs, CNE6 and MG13, which exhibited the highest trimer content and stability at a level comparable to the subtype A reference, BG505. Replacing the gp41 ectodomain (gp41ECTO) of CRF01_AE trimers with that of CNE6, MG13, and BG505 resulted in chimeric constructs with significantly improved trimer content and stability. Negative-stain electron microscopy (EM) confirmed the structural integrity of these chimeric UFO trimers with CNE6 gp41ECTO. Antibody binding assays showed that the chimeric trimers shared similar antigenic profiles to those with their original gp41ECTO domains. Our results thus revealed the intrinsic differences among HIV-1 Envs of diverse origins and the critical role of gp41ECTO in stabilizing the trimeric spike. By taking advantage of naturally stable Envs, gp41ECTO swapping may represent a universal approach for the generation of stable trimers with the desired structural and antigenic properties for downstream in vivo evaluation and vaccine development.